Direct Selling Program Strategy Through Online Reporting System Design With ”Ipa & Qfd” Method (Case Study at PT. Global Green Trading) - Shilul Imaroh, T; ., Reza (KnE Social Sciences, 2018)
This study aims to determine the attributes that become the perceptions and expectations of salespeople and determine the importance of the attributes on the system to be designed, and to know the design of online reporting system in accordance with the wishes of consumers. This research was conducted at PT. Global Green Trading from May until September 2017 with a sample of 30 salespeople and data analysis was done using Importance–Performance Analysis and House of Quality matrix that is a form of QFD representation. The results showed that the most important attributes of salesperson in the design of online reporting system of direct selling program is the level of easiness access, the level of easiness in finding information, the availability of information in the presentation of data, the easiness of conducting transactions, the availability of information related to the products offered, and easiness in obtaining the desired information. The result of Importance Performance Analysis shows that every attribute is very important for salespeople so that reporting with this online system can be implemented immediately so that salespeople can be better in doing the activity. The design of online reporting system in accordance with the wishes of the salesperson that is the completeness of the menu, available information required, easiness in the presentation of data, the availability of transaction menu, the visualization of products offered, and easiness of accessing information. Keywords: designing, online reporting system, direct marketing